Picobirnaviruses: prevalence, genetic diversity, detection methods - A. Yu. Kashnikov; N. V. Epifanova; N. A. Novikova (Вавиловский журнал генетики и селекции)
This article presents a general overview of the prevalence, genetic diversity and detection methods of picobirnaviruses (PBVs), which are small, non-enveloped icosahedral viruses with a segmented double-stranded RNA genome consisting of two segments taxonomically related to the genus Picobirnavirus of the family Picobirnaviridae. This review of scientific papers published in 1988–2019 provides data on the PBV distribution in the nature and a broad host range. PBV infection is characterized as opportunistic, the lack of understanding of the etiological role of PBVs in diarrhea is emphasized, since these viruses are detected both in symptomatic and asymptomatic cases. The concept of PBV infection as a chronic disease caused by a long-lasting persistence of the virus in the host is considered. Such factors as stress syndrome, physiological conditions, immune status and host age at the time of primary PBV infection influence the virus detection rate in humans and animals. The possible zoonotic nature of human PBV infection is noted due to the capacity for interspecies PBV transmission acquired during evolution as a result of the reassortment of the genome segments of different viruses infecting the same host. Data providing evidence that PBVs belong to eukaryotes and a challenging hypothesis stating that PBVs are bacterial viruses are presented. The need to intensify work on PBV detection because of their wide distribution, despite the complexity due to the lack of the cultivation system, is emphasized. Two strategies of RT-PCR as main PBV detection methods are considered. The genomes of individual representatives of the genus isolated from different hosts are characterized. Emphasis is placed on the feasibility of developing primers with broader specificity for expanding the range of identifiable representatives of the genus PBV due to a huge variety of their genotypes. The importance of effective monitoring of PBV prevalence for studying the zoonotic and anthroponotic potential using metagenomics analysis is highlighted, and so is the possibility of using PBV as a marker for environmental monitoring.